NICE guidance to working with real-world data - A. Sh. Motrinchuk; A. R. Kasimova; E. A. Novoderezhkina (Реальная клиническая практика: данные и доказательства, 2023)
This article provides a brief overview of the key aspects of planning, conducting, and reporting NICE clinical practice data collection and analysis studies, as well as general information about the sources of real-world data (RWD) and their use in NICE management decision-making algorithms. The difficulties of finding and using RWD are described, as well as methods for overcoming them, brief NICE recommendations for assessing the suitability of data and an algorithm for conducting quantitative studies to collect evidence from RWD are given.